South Asian origin and global transmission history of Mycobacterium tuberculosis lineage 4 - Bharkbhoom Jaemsai; Prasit Palittapongarnpim; Pakorn Aiewsakun (mSystems)
ABSTRACT The origin and transmission history of Mycobacterium tuberculosis lineage 4 (MTB L4) has been extensively studied. However, different studies yielded different results; thus, the evolutionary history of MTB L4 still remains a subject of debate. Recently, a substantial amount of whole-genome sequencing data of MTB has become available, providing new data from diverse geographical locations worldwide. This study analyzed the most comprehensive global collection of MTB L4 genomes to date (n = 11,154), including new sequences from previously under-represented regions, to re-examine the bacterial evolutionary history. Our results suggest that the bacteria likely emerged and diversified in South Asia during the 12th and 13th centuries and then spread to various Old-World regions and the Americas between the 15th and 16th centuries, before undergoing extensive intercontinental transmissions starting from the 17th century onward. The effective population size of MTB L4 as a whole was estimated to expand steadily throughout its evolutionary history until the mid-20th century when a sharp drop occurred, coinciding with the introduction of antibiotics and significant improvements in human living conditions. Interestingly, this pattern was consistently observed across all major sub-lineages, indicating a broad impact of these factors on MTB L4 as a whole. Altogether, our results offer new refined insights into how anthropological changes might have shaped the bacterial evolutionary history and ultimately its global geographical distribution we observe today.IMPORTANCEContrary to previous studies, our analysis suggests that Mycobacterium tuberculosis lineage 4 (MTB L4) likely emerged and diversified in South Asia during the 12th and 13th centuries. It then spread to both the Americas and other Old-World regions between the 15th and 16th centuries, followed by extensive intercontinental transmissions beginning in the 17th century. These findings suggest that South Asia, one of the main crossroads of historical trade networks, might have played a pivotal role in promoting the early intercontinental spread of MTB L4. The effective population size of all major MTB L4 sub-lineages was inferred to increase steadily until the mid-20th century, after which a decline was observed. This decline coincides with the advent of antibiotics and improved living conditions, suggesting a wide impact of these factors on the entire bacterial population.